Exploring patterns of beta‐diversity to test the consistency of biogeographical boundaries: A case study across forest plant communities of Italy. Issue 20 (2nd October 2019) - Chiarucci, Alessandro; Nascimbene, Juri; Campetella, Giandiego; Chelli, Stefano; Dainese, Matteo; Giorgini, Daniele; Landi, Sara; Lelli, Chiara; Canullo, Roberto
Abstract: Aim: To date, despite their great potential biogeographical regionalization models have been mostly developed on descriptive and empirical bases. This paper aims at applying the beta‐diversity framework on a statistically representative data set to analytically test the consistency of the biogeographical regionalization of Italian forests. Location: Italy. Taxon: Vascular plants. Methods: Forest plant communities were surveyed in 804 plots made in a statistically representative sample of forest communities made by 201 sites of Italian forests across the three biogeographical regions of the country: Alpine, Continental, and Mediterranean. We conducted an ordination analysis and an analysis of beta‐diversity, decomposing it into its turnover and nestedness components. Results: Our results provide only partial support to the consistency of the biogeographical regionalization of Italy. While the differences in forest plant communities support the distinction between the Alpine and the other two regions, differences between Continental and Mediterranean regions had lower statistical support. Pairwise beta‐diversity and its turnover component are higher between‐ than within‐biogeographical regions. This suggests that different regional species pools contribute to assembly of local communities and that spatial distance between‐regions has a stronger effect than that within‐regions. Main conclusions: Our findings confirm a biogeographical structure of the species pools that is captured by the biogeographical regionalization. However, nonsignificant differences between the Mediterranean and Continental biogeographical regions suggest that this biogeographical regionalization is not consistent for forest plant communities. Our results demonstrate that an analytical evaluation of species composition differences among regions using beta‐diversity analysis is a promising approach for testing the consistency of biogeographical regionalization models. This approach is recommended to provide support to the biogeographical regionalization used in some environmental conservation polices adopted by EU. Abstract : This paper aims at applying the beta‐diversity framework on a statistically representative data set to test the consistency of the biogeographical regionalization of Italian forests based on the three different regions recognised within the country. Our results provide only partial support to the consistency of the biogeographical regionalization of Italy based on three regions. Our findings support the existence of a biogeographical structure of the species pools that is captured by the biogeographical regionalization. However, nonsignificant differences between the Mediterranean and Continental biogeographical regions suggest a weakness in this biogeographical regionalization.